Hitler's mountain : the Führer, Obersalzberg and the American occupation of Berchtesgaden - Mitchell, Arthur (McFarland, 2007)
"This work examines the political events that took place in Obersalzberg from the 1920s until the U.S. Army returned control of the area to the German government in 1995. Concentrating primarily on the years when Hitler was in residence, it discusses his original acquaintance with Berchtesgaden and focuses on the symbolism of self-identity and public perception"--Provided by publisher.